2019
DOI: 10.1093/hmg/ddz271
|View full text |Cite
|
Sign up to set email alerts
|

G2019S-LRRK2 mutation enhances MPTP-linked Parkinsonism in mice

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease with a heterogeneous etiology that involves genetic and environmental factors or exogenous. Current LRRK2 PD animal models only partly reproduce the characteristics of the disease with very subtle dopaminergic neuron degeneration. We developed a new model of PD that combines a sub-toxic MPTP insult to the G2019S-LRRK2 mutation. Our newly generated mice, overexpressing mutant G2019S-LRRK2 protein in the brain, displayed a mild, age-dependent progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…The wild-type LRRK2 transgenic mice showed the motor abnormalities even at 12 months of age but significantly differed compared to control mice. Their data showed that the LRRK2 overexpression in mice escalated dopaminergic neurons’ loss when exposed to MPTP doses and suggested that the LRRK2 gene/MPTP interaction mice model could be a useful tool for better understanding in PD investigations [ 152 ]. Guo et al (2016) administered a cumulative dose of 80 mg/kg MPTP (20 mg/kg, four intraperitoneally) in male C57BL/6 mice models.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…The wild-type LRRK2 transgenic mice showed the motor abnormalities even at 12 months of age but significantly differed compared to control mice. Their data showed that the LRRK2 overexpression in mice escalated dopaminergic neurons’ loss when exposed to MPTP doses and suggested that the LRRK2 gene/MPTP interaction mice model could be a useful tool for better understanding in PD investigations [ 152 ]. Guo et al (2016) administered a cumulative dose of 80 mg/kg MPTP (20 mg/kg, four intraperitoneally) in male C57BL/6 mice models.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…A recent LRRK2 phosphomimetic (S910A + S935A) KI mouse model has shown a reduction in astrogliosis, while a transgenic OE of LRRK2-G2019S in mice exhibited an increase in astrogliosis (Xiong et al, 2018;Zhou et al, 2018). Another study using G2019S KI mice has exhibited astrogliosis using a sub-toxic dose of MPTP dose to cause DA neurodegeneration (Arbez et al, 2019). Investigation of LRRK2 and astrogliosis using these models may help elucidate potential pathogenic mechanisms for LRRK2 in the CNS.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Neurodegeneration associated with LRRK2 G2019S expression is augmented in mice after MPTP administration; however, mice expressing human WT LRRK2 exhibit similar response to MPTP as non-transgenic animals [114,115]. Sub-toxic exposure to MPTP increases motor impairment, dopaminergic cell loss, and astrocyte activation, which can be partially reversed by pharmacological LRRK2 kinase inhibition [115]. On the other hand, mice that lack LRRK2 kinase domain do not show any difference in MPTP sensitivity when compared to WT animals [116].…”
Section: Increased Susceptibility To Synthetic Toxicants In Lrrk2 Animentioning
confidence: 99%
“…1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP), a contaminant of the synthetic opiate meperidine, was identified as a neurotoxic compound leading to an acute form of parkinsonism [112,113]. Neurodegeneration associated with LRRK2 G2019S expression is augmented in mice after MPTP administration; however, mice expressing human WT LRRK2 exhibit similar response to MPTP as non-transgenic animals [114,115]. Sub-toxic exposure to MPTP increases motor impairment, dopaminergic cell loss, and astrocyte activation, which can be partially reversed by pharmacological LRRK2 kinase inhibition [115].…”
Section: Increased Susceptibility To Synthetic Toxicants In Lrrk2 Animentioning
confidence: 99%